THE RELATION USE OF GADGET WITH ADDED MYOPIA VALUE IN STUDENTS - Perceka, Andhika Lungguh; Ratnasari, Devi; Lestari, Lia Intan (Karsa Husada Health Institute Garut, 2024)
The use of gadgets is very closely related to human life. Gadgets have become one of the most important things for most people, during and especially after the Covid-19 pandemic, individuals are encouraged to maintain physical distance and limit outings. As a form of diversion from these restrictions, people spend more time using gadgets for work, study, communication or for entertainment. Poor use of gadgets will have an impact on visual acuity and cause an increase in the added myopia value. The purpose of this research was to determine the relationship between use of gadget and the added myopia value in students at Karsa Husada Health Science Institute Garut. The research method used is a quantitative approach with a crosssectional research design, the population in this study is 1672 students and a sample of 95 respondents is obtained using a random sampling technique using the Startified Random Sampling method. The data was collected using a questionnaire statement on the use of gadgets and a statement of the added myopia value then the data was examined. using the Chi Square test. The results of this research indicate that there is a significant relationship between the use of gadgets and added myopia value in students at Karsa Husada Health Institute Garut. And it can be inferred that there is a notable correlation between gadget usage and the added myopia value in students at Karsa Husada Health Science Institute Garut. Suggestions from